RAC3 Inhibition Induces Autophagy to Impair Metastasis in Bladder Cancer Cells via the PI3K/AKT/mTOR Pathway - Wang, Liwei; Shi, Jiazhong; Liu, Sha; Huang, Yaqin; Ding, Hua; Zhao, Baixiong; Liu, Yuting; Wang, Wuxing; Yang, Jin; Chen, Zhiwen (Frontiers in Oncology, 2022)
Background: Bladder cancer (BCa) is one of the most frequent malignant tumors globally, with a significant morbidity and mortality rate. Gene expression dysregulation has been proven to play a critical role in tumorigenesis. Ras-related C3 botulinum toxin substrate3 (RAC3), which is overexpressed in several malignancies and promotes tumor progression, has been identified as an oncogene. However, RAC3 has important but not fully understood biological functions in cancer. Our research aims to reveal the new functions and potential mechanisms of RAC3 involved in BCa progression Methods: We explored the expression level of RAC3 and its relationship with prognosis by publicly accessible BCa datasets, while the correlation of RAC3 expression with clinicopathological variables of patients was analysed. In vitro and in vivo proliferation, migration, autophagy, and other phenotypic changes were examined by constructing knockdown(KD)/overexpression(OE) RAC3 cells and their association with PI3K/AKT/mTOR pathway was explored by adding autophagy-related compounds. Results: Compared with non-tumor samples, RAC3 was highly expressed in BCa and negatively correlated with prognosis. KD/OE RAC3 inhibited/promoted the proliferation and migration of BCa cells. Knockdown RAC3 caused cell cycle arrest and decreased adhesion without affecting apoptosis. Inhibition of RAC3 activates PI3K/AKT/mTOR mediated autophagy and inhibits proliferation and migration of BCa cells in vivo and in vitro. Autophagy inhibitor 3MA can partially rescue the metastasis and proliferation inhibition effect caused by RAC3 inhibition. Inhibit/activate mTOR enhanced/impaired autophagy, resulting in shRAC3-mediated migration defect exacerbated/rescued. Conclusion: RAC3 is highly expressed in BCa. It is associated with advanced clinicopathological variables and poor prognosis. Knockdown RAC3 exerts an antitumor effect by enhancing PI3K/AKT/mTOR mediated autophagy. Targeting RAC3 and autophagy simultaneously is a potential therapeutic strategy for inhibiting BCa progression and prolonging survival.